34. VIDEO ENDOSCOPIC INGUINAL LYMPHADENECTOMY IN FIRST 14 PATIENTS WITH PENILE SQUAMOUS CELL CARCINOMA AT BINH DAN HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Inguinal lymph node involvement is an important prognostic factor in penile cancer. Inguinal lymph node dissection allows staging and treatment of inguinal nodal disease. However, it causes morbidity and is associated with complications such as lymphocele, skin loss, and infection. Aims: To evaluate the results of video endoscopic inguinal lymphadenectomy (VEIL) in patients with penile squamous cell carcinoma at Binh Dan hospital. Materials and Methods: It is a cohort study, 14 patients underwent VEIL in 2022. Data analyzed included mean operative time, mean lymph node yield, complications, recurrent rate and survivl rate. Results: The mean age of patients was 50.8 years (range: 44–58 years). Mean operative time for VEIL was 203,3 min (130–250 min). Mean lymph node yield was 8,3(range: 6-12 nodes). No intraoperative complication was experienced during the series. We noted that 1 case has surgical emphysema on 1 groin (7,1%), 2 cases have localized lymphocele (14,2%). After 1 year, no recurrent case andh survival rate is 100%. Conclusions: VEIL is a safe and feasible technique in patients with penile carcinoma who require radical inguinal lymphadenectomy. It allows the removal of inguinal lymph nodes and reduces surgical morbidity substantially.
Keywords: Penile cancer, video endoscopic inguinal lymphadenectomy.